A Multiscale drusen growth model for Age‐related Macular Degeneration. Issue 1 (14th December 2021) - Timothy, Jithender J.; Holla, Vijaya; Meschke, Günther
Abstract: Age‐related macular degeneration (AMD) is the leading cause of vision loss in older adults above the age of 50. AMD is attributed to the degeneration and loss of normal function of the outer retina in the macular region. Presence of extracellular material called drusen between the Bruch's membrane (BrM) and the retinal pigment epithelium (RPE) is the hallmark of AMD. Moreover, thickening and reduced diffusivity of the BrM has been observed in patients with AMD. In this paper, we develop a mulitscale Drusen growth model to test the hypothesis that the BrM thickening and Drusen generation could be a coupled process such that the BrM thickening causes hypoxic stress at RPE which leads to generation of more drusen at POS and vice versa. The proposed framework comprises of a cascade lattice micromechanics model for characterizing the overall diffusivity of the BrM, a finite element model for simulating oxygen transport from the vascular system to the photoreceptors and a cellular potts model for simulating morphological changes to the outer retina due to drusen development. Simulation results are analysed at different time steps and implications of the potential chain reaction on Drusen growth and RPE, POS cell deterioration are discussed.